Relação entre poluição do ar e baixo peso ao nascer. - Silva, Macerlane de Lira (2017)
Introduction: Birth weight is one of the main factors of neonatal morbidity, being determinant for survival conditions in early childhood. Studies have shown correlations between exposure to air pollution and low birth weight (LBW). Objective: To analyze the relationship between air pollution and LBW from the information contained in the Birth Information System that occurred in the city of São Paulo, SP, between 2011 and 2015. Method: The present ecological study with an individual, retrospective base. Data about air pollutants and climatic variables were obtained from Environment Company of the State of São Paulo (CETESB). For data analyses, it was used the software SPSS. Quantitative variables were presented in terms of their values (media) and dispersion (standard deviation) values and the qualitative variables were presented in terms of their absolute and relative values. To verify the association between birth weight (normal or LW), maternal age (aging rate), marital status, education, type of pregnancy, number of prenatal consultations, type of delivery, gender of the newborn it was used the Square QI-test. Aiming to verify the relationship between LW at birth and air pollution, it was used the logistic regression model, adjusted for mean humidity, minimum temperature, maternal schooling, maternal age, number of prenatal consultations, type of pregnancy and type of delivery. The level of significance was 5%. Results: During the study period, the results showed that 327,675 births were recorded in SINASC. From these, 31,161 (9.5%) were born with LW and 296,514 (90.5%) with adequate weight. It was observed a prevalence of males (51.1%), born with adequate gestational age (87.2%), by a cesarean delivery (54.0%), having the pregnant women attended 7 or more prenatal consultations (74,9%). The majority of mothers had 7 years or more of studies (86.4%). Data analysis revealed that mothers under 20 and over 35 years old had 1.15 (CI95%: 1.11-1.20) and 1.16 (CI95%: 1.12-1.20) more chances to have newborns with LW than mothers aged between 20 and 35 years, pregnant women who performed less than 7 prenatal visits had 1.16 (CI95%: 1.12-1.21), as did non-married pregnant-women presented 1.14 (CI95%: 1.11-1.18) times more of chances of having a new born with LW. Prematurity appears with a predictive value of birth with LW of 25.74 (CI95%: 25.04-26.46). Only SO2 had a significant effect with the low weight presented. For each increase of an interquartile at the level of SO2 within the three trimesters of gestation, an increase in the occurrence of LW of newborns. Conclusion: There are many deleterious health effects due to pollution, especially the exposure of women in the gestational period, leading to LWB.